Myval: A Novel Transcatheter Heart Valve for the Treatment of Severe Aortic Stenosis - Ashok Seth; Vijay Kumar; Vivudh Pratap Singh; Dhananjay Kumar; Puneet Varma; Vishal Rastogi (Interventional Cardiology: Reviews, Research, Resources)
Transcatheter aortic valve implantation (TAVI) performed using femoral arterial access is now a guideline recommended treatment for severe calcific aortic stenosis (AS) in elderly patients. Technological advancements and procedural refinements have focused on making TAVI simpler, safer, more effective and durable. Myval (Meril Lifesciences) is a new generation balloon-expandable transcatheter heart valve (THV) developed in India that possesses novel features to improve deliverability and aid precise deployment. Following the first-in-human study, Myval was approved in India for commercial implantation in October 2018 and was subsequently given a CE mark in April 2019. This article reviews the science, technology and up-to-date clinical evidence for the Myval THV.